Formation of multiple subjectivity (on examples of B. Pascal and S. Kierkegaard) - Tetenkov, Nikolay Borisovich (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to one of the topical themes of modern philosophy – multiple subjectivity. In philosophy, the examples of multiple subjectivity are S. Kierkegaard and B. Pascal. To identify the factors contributing to the emergence of multiple subjectivity, the article compares the biographies of S. Kierkegaard. Comparative analysis allows us to identify these factors, which include education, family education, intellectual environment, complex, synthetic thinking, literary creativity.